Model Keterampilan Bantingan Lengan Olahraga Gulat Untuk Atlet Pemula - Mahyudi Yudi; Hernawan (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2020)
This study aims to produce a wrestling model of arm-throwing skills. Research on the development of an arm-throwing skill model for novice athletes using the Research & Development method from Borg and Gall. The subjects in this development research involved 30 athletes in PPLP wrestling, Pengprov PGSI and Platinum Wrestling Club. This study resulted in 12 arm-throwing model skills and firstly the model skills were validated by a validation team consisting of coaches and wrestling sports experts. Based on the results of a small group test involving 8 athletes from 1 club, it shows that of the 20 variations developed, 12 of them are eligible to be tested on a wider sample. The results of the large group test conducted by researchers involved 30 people from the PPLP and the Plaitnum Wrestling Club. Based on the results of the study, 12 models of arm skills skills can be used after evaluation by the validator team, the results of the small group test and the large group test results are declared feasible and valid to be used as a model in wrestling arm throwing exercise so that it can improve multilateral motion in athletes. young people serve and also exercise more effectively and efficiently so as to increase the interest and motivation of regional athletes in participating in wrestling exercises, especially arm throwing techniques.